The Ideal of a Radical Christian Intellectual - Hogue, William (Religions, 2018)
The life and work of Ignacio Ellacuría, S.J. is of radical vision and revolutionary change. His dynamic life and works accompanied El Salvador and the Universidad Centroamericana through perhaps the most tumultuous years of the country's history, yet there has been limited work done to examine his contributions. This paper shows how Ellacuría viewed the role of a Christian intellectual and Christian university within his philosophical and theological framework. I argue that Ignacio Ellacuría held, similarly to his soteriological views, that the intellectual must also be willing to sacrifice all for the sake of her/his work in a pattern of discipleship/martyrdom that is prefigured by his exemplars Christ and Socrates. It was this dedication to praxis and theory that western theology and philosophy had respectfully lost since their foundations, which he sought to restore to a central role. In conclusion, the Christian intellectual and institution, according to Ellacuría, must use its voice and life in service of the people even to the point of martyrdom; he would argue, the implicit reason for Christian martyrdom and the crucifixion of Christ himself.